2019
DOI: 10.1038/s41598-019-40849-3
|View full text |Cite
|
Sign up to set email alerts
|

Rice seed priming with sodium selenate: Effects on germination, seedling growth, and biochemical attributes

Abstract: The aim of this study was to determine the effects of sodium selenate (15, 30, 45, 60, 75, 90, and 105 mg kg−1) on the germination and seedling growth of Changnongjing 1 rice (Oryza sativa L.) at 25 °C and 30 °C. Low selenate concentrations induced shorter and more uniform germination periods than did ultrapure water at both temperatures. Seedlings primed with low selenate concentrations were superior to those primed with ultrapure water in terms of plant height, fresh weight, dry matter accumulation, and solu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
34
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 61 publications
(39 citation statements)
references
References 31 publications
(39 reference statements)
4
34
1
Order By: Relevance
“…However, there were no significant differences in shoot and root length, leaf area, leaf weight (Table 2 and Table 3). Du et al (2019) also reported that seedlings primed with low selenite concentration were superior to those primed with water, as indicated by higher fresh weight, dry weight, soluble carbohydrate, and protein content in selenite-primed seedlings…”
Section: Seed Emergence and Seedling Growthmentioning
confidence: 90%
“…However, there were no significant differences in shoot and root length, leaf area, leaf weight (Table 2 and Table 3). Du et al (2019) also reported that seedlings primed with low selenite concentration were superior to those primed with water, as indicated by higher fresh weight, dry weight, soluble carbohydrate, and protein content in selenite-primed seedlings…”
Section: Seed Emergence and Seedling Growthmentioning
confidence: 90%
“…Recent studies also showed inhibition of germination when seeds were submitted to increasing Se concentrations (Du et al 2019). Prins et al (2011) studied the effect of selenate on the reproductive functions of accumulating and hyperaccumulating species of Se.…”
Section: Effect Of Se On Germination and Early Growth Development Of mentioning
confidence: 99%
“…Fragrant rice cultivars are known for their good quality and the unique aroma, with 2‐acetyl‐1‐pyrroline (2‐AP) as the key component (Wakte et al., 2017). Many researchers have attempted to improve the aroma and grain yield of fragrant rice in the transplanted production system with different crop management strategies, such as nitrogen fertilizer, alternate wetting and drying irrigation, extra silicon application, and soil puddling (Bao et al., 2018; Du, Luo, He, Mao, et al., 2019; Mo et al., 2017; Mo et al., 2019). Bao et al.…”
Section: Introductionmentioning
confidence: 99%
“…Several workers of our team also discovered that applications of Se regulated the growth and development of rice. For example, seed priming with low‐concentration Se (15–90 mg L −1 ) increased the growth and development of rice seedlings and enhanced the activities of both peroxidase and superoxide dismutase (Du, Luo, He, Zhang, et al., 2019). Foliar application of sodium selenate at initial heading stage with suitable concentrations (20–50 μmol L −1 ) significantly enhanced the activities of 2‐AP–related enzymes such as P5CS, PRODH, and OAT and increased the grain 2‐AP concentration of fragrant rice cultivars (Luo, Du, et al., 2019).…”
Section: Introductionmentioning
confidence: 99%